2018
DOI: 10.1016/j.rmcr.2018.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Catheter directed thrombolysis combined with ECMO for massive pulmonary emboli

Abstract: This case report discusses a previously healthy young male who suffered an in hospital cardiac arrest, found to be secondary to massive pulmonary emboli (PE). This patient was not a candidate for PE dosing of tPA, but continued to have worsening cardiogenic shock and acute hypoxic respiratory failure. The decision was made to initiate venoarterial extracorporeal membrane oxygenation (VA ECMO) in combination with catheter assisted thrombolysis.With time, the sequelae of his disease process changed. Although his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…About 77 studies were included in this review (Fig. 1) and were assessed for bias using Joanna Briggs Institute Critical Appraisal Checklist for Systematic Reviews and Research Syntheses (19–95). Our review considered articles to have a low risk of bias if all checklist criteria were met, moderate risk if greater than or equal to 75% of criteria were met, and high risk if less than 75% of criteria were met.…”
Section: Methodsmentioning
confidence: 99%
“…About 77 studies were included in this review (Fig. 1) and were assessed for bias using Joanna Briggs Institute Critical Appraisal Checklist for Systematic Reviews and Research Syntheses (19–95). Our review considered articles to have a low risk of bias if all checklist criteria were met, moderate risk if greater than or equal to 75% of criteria were met, and high risk if less than 75% of criteria were met.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, if we consider the ECMO's physiology of partial cardiopulmonary bypass, VA ECMO is the most suitable device for the pathophysiology of right heart failure from PTE. After the patient becomes stable, the treatment for the thrombus should be selected among the following options: anticoagulation,25)29) systemic thrombolysis,30) catheter-directed thrombectomy or thrombolysis,31) or surgical embolectomy 24)26). The European Society of Cardiology 2014 acute PTE guidelines briefly mention that ECMO can be used to treat massive PTE as a method for hemodynamic support and as an adjunct to surgical thrombectomy 32).…”
Section: Indications Of Venoarterial Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
“…The European Society of Cardiology 2014 acute PTE guidelines briefly mention that ECMO can be used to treat massive PTE as a method for hemodynamic support and as an adjunct to surgical thrombectomy 32). Because VA ECMO itself requires systemic anticoagulation, VA ECMO with or without catheter-directed thrombectomy may cure acute PTE 31). Thrombolysis, especially systemic thrombolysis, would to be dangerous under VA ECMO.…”
Section: Indications Of Venoarterial Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
“…The patient was weaned off inotropic support by the end of the procedure and had no major bleeding. Giuffrida et al, 7 Nelson et al, 8 and Lindsey et al 9 all reported the use of USAT in patients following cardiac arrest with concerns for trauma as a result of cardiopulmonary resuscitation. Gowda et al 10 illustrated the application of USAT in a pregnant patient at 9 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%